The Effectiveness of American Films Without Subtitles in Improving Students’ English Listening Skills: Efektivitas Film Amerika Tanpa Subtitel dalam Meningkatkan Kemampuan Mendengarkan Bahasa Inggris Siswa - Dillo Sarwana; Deasy Yunita Siregar; Karunia Amanda Z; Khairuna Zahra; Nazla Aliyah Alfitah (JURNAL ILMIAH RESEARCH STUDENT, 2026)
ABSTRACT The use of film as a learning medium in the classroom is often seen as less relevant and meaningful in teaching listening comprehension. This perception arises because film is an authentic material that is considered not fully in accordance with pedagogical goals, so its use in learning is still limited. This article aims to examine the effectiveness of film as an alternative medium in teaching listening comprehension. The discussion included common problems faced by students during film screening activities, techniques for applying film in learning, and listening activities that can be done in class. The results of the study show that the use of film in teaching listening comprehension is able to increase student motivation, engagement, and interest in learning.